2002
DOI: 10.1007/s007260200022
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the rate of synthesis of nitric oxide by Mg 2+ and hypoxia. Studies in rat heart mitochondria

Abstract: In isolated rat heart mitochondria, L-arginine is oxidized by a nitric oxide synthase (mtNOS) achieving maximal rates at 1 mM L-arginine. The NOS inhibitor N(G)-nitro-L-arginine methyl ester (NAME) inhibits the increase in NO production. Extramitochondrial free magnesium inhibited NOS production by 59% at 3.2 mM. The mitochondrial free Mg(2+) concentration increased to different extents in the presence of L-arginine (29%), the NO donor (S-nitroso-N-acetylpenicillamine) (105%) or the NOS inhibitors L-NAME (48%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Indeed, heart mtNOS activity is dependent on cation concentration in the reaction medium. Extramitochondrial free Mg 2ϩ , a well-known mitochondrial Ca 2ϩ uniporter blocker, inhibits NO production in rat heart mitochondria by 60% in a dose-dependent manner (91,143). This concept is in agreement with other reports (40,41) showing that blocking the mitochondrial Ca 2ϩ uniporter with ruthenium red inhibits mitochondrial NO production.…”
Section: Heart Nosssupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, heart mtNOS activity is dependent on cation concentration in the reaction medium. Extramitochondrial free Mg 2ϩ , a well-known mitochondrial Ca 2ϩ uniporter blocker, inhibits NO production in rat heart mitochondria by 60% in a dose-dependent manner (91,143). This concept is in agreement with other reports (40,41) showing that blocking the mitochondrial Ca 2ϩ uniporter with ruthenium red inhibits mitochondrial NO production.…”
Section: Heart Nosssupporting
confidence: 82%
“…Interestingly, substrate-energized heart mitochondria produce NO without additional supplementation with Ca 2ϩ (128), indicating that the concentration of Ca 2ϩ in the mitochondrial preparation may be sufficient to sustain a basal mtNOS activity. Nevertheless, the functional studies performed on cardiac mitochondria isolated from mice (70,72) or rats (91,115,126,140,141,143) demonstrated the activation of mitochondrial NO production upon addition of Ca 2ϩ to the reaction medium. Taking into account that heart mitochondrial matrix Ca 2ϩ concentrations differ from cytosolic Ca 2ϩ concentrations (39,85), the existence of a Ca 2ϩ -dependent NOS within mitochondria has significant consequences in terms of the differential regulation of this enzyme.…”
Section: Heart Nossmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the nitrotyrosine immunoreactivity intensities, the patterns after reoxygenation in the presence of L-arginine were independent of the duration of hypoxia-anoxia and mirrored the pattern exhibited by mitochondria before hypoxia-anoxia. These results suggest that the same proteins become selectively nitrated during reoxygenation, a condition of oxidative and nitrative stress (23,24,47) generated via excessive superoxide formation (20) along with the full recovery of ⅐ NO production (34). Nevertheless, the high selectivity and rapid turnover of the nitro groups at the target proteins during a "denitration-nitration" cycle suggest that this process is more than simply oxidant damage and clearance.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have shown Ca 2+ sensitivity of mtNOS in various organs, tissues, and cells [19,[36][37][38]. However, an earlier study suggested that mtNOS is not Ca 2+ sensitive and its activity is stimulated by supplementing mitochondria with L-arginine [39].…”
Section: Ca 2+ -Dependence Of Heart Mtnosmentioning
confidence: 99%